Avaliação do enfrentamento da hospitalização em crianças por meio de instrumentos informatizados - Moraes, Elissa Orlandi (2007)
Child hospitalization may bring about psychological problems, such as depression and stress due to routine changes and invasive procedures. It is worth, then, identifying the hospitalization coping strategies, emphasizing the playing as a facilitator of the child adjustment to the hospital setting. The psychological assessment in the hospital environment implies in controlling several variables; and it is made easier by means of IT based resources. This research analyzed the hospitalization coping strategies and playful activities by means of IT instruments. Twenty-eight (28) children (20 boys; aged 6-12) admitted to a public hospital in the city of Vila Velha/ES and their parents were subjects of this research. They answered the Child Behavior Checklist (CBCL, aged 6-18) as well as provided data about the routine of their children who in turn answered Hospitalization Coping IT Based Instruments (AEHcomp), with 20 facilitating and non-facilitating hospitalization scenarios, in addition to the IT Based Assessment of Playing Activities in the Hospital (ABHcomp), with 20 playful activities. Data about pathologies and hospital admissions was gathered. Seventeen (17) children were referred to in the CBCL. The plays chosen most often (ABHcomp) were: watching TV (average = 3,4) and playing minigame (average = 3,0), supported by nonexplanatory answers (50,2%) or by the play context (19,6%). The AEHcomp, presented more facilitating answers to the hospitalization (average = 1,8), such as talking (100%) and taking medicine (100%), than non-facilitating (average = 0,9), as being sad (71,4%) and crying (75%). Among 13 coping strategies, rumination (28,6%) and distraction (20,1%) were the most common. There were no correlations between behavioral problems prior to the hospitalization and nonfacilitating behaviors. There was a significant correlation of facilitating behaviors only related to age and routine changes. This assessment may provide subsidies in intervention towards children, thus preventing emotional damages caused by the hospital setting.